2012
DOI: 10.14341/2306-3513-2012-2-15-20
|View full text |Cite
|
Sign up to set email alerts
|

Autoantibody profiling of benign and malignant thyroid tumors and design of a prototype diagnostic array

Abstract: На сегодняшний день "золотым стандартом" в диагностике опухолей щитовидной железы (ЩЖ) является тонкоиголь ная аспирационная биопсия (ТАБ). Однако ТАБ в 15-30% наблюдений не позволяет дифференцировать доброкачест венную природу опухоли от злокачественной. В целях поиска дополнительных индикаторов в предоперационной дифференциальной диагностике опухолей ЩЖ нами исследован диагностический потенциал 3 кандидатных раково ассоциированных антигенов в клинической группе 22 доброкачественных и 26 злокачественных опухо… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…In a somewhat similar study, we used a mini-array of 21 recombinant TAAs identified in non-thyroid human cancers to test their serological reactivity in 26 DTC and 22 FTA patients [ 141 ]. We were able to ultimately identify a three-features TAA signature (ankyrin repeat domain containing-protein 30A ANKRD30A, also known as NY-BR-1; regulator of G protein signaling 5 RGS5; and a particular isoform of hydrocephalus-inducing 2 HYDIN2 - KIAA1864) capable of significantly discriminating DTC from FTA cases both using individual TAAs (DSn of 19% for each; DSP of 95–100%) ( Figure 2 ) and combined three-features TAA panel (DSn of 50%; DSp of 95%).…”
Section: The Tumor-associated Antigens (Taas) and Their Cognate Autoa...mentioning
confidence: 99%
“…In a somewhat similar study, we used a mini-array of 21 recombinant TAAs identified in non-thyroid human cancers to test their serological reactivity in 26 DTC and 22 FTA patients [ 141 ]. We were able to ultimately identify a three-features TAA signature (ankyrin repeat domain containing-protein 30A ANKRD30A, also known as NY-BR-1; regulator of G protein signaling 5 RGS5; and a particular isoform of hydrocephalus-inducing 2 HYDIN2 - KIAA1864) capable of significantly discriminating DTC from FTA cases both using individual TAAs (DSn of 19% for each; DSP of 95–100%) ( Figure 2 ) and combined three-features TAA panel (DSn of 50%; DSp of 95%).…”
Section: The Tumor-associated Antigens (Taas) and Their Cognate Autoa...mentioning
confidence: 99%